Conversations on the Global South – Locating Duterte in Davao: An Interview with Jose Jowel Canuday - Canuday, Jose Jowel (Archīum Ateneo, 2017)
Since our last issue, the new strongman president of the Philippines, Rodrigo Duterte, has captured the attention of local and international news. He has been a controversial president, waging a war on drugs that has led to as many as 7,000 deaths according to some news reports and human rights advocates. Commentators in the Philippines and abroad continue to ask: What explains his continued popularity? For this installment of “Conversations on the Global South,” our Managing Editor, Jose Jowel Canuday (JC) removes his editorial hat and recalls the many years he spent as a journalist in Duterte’s home city of Davao. Prior to being an academic, Canuday was a pioneering journalist in Davao, covering various issues from agrarian reform, displacement, and human rights. For this interview, he talks to editor Lisandro E. Claudio (LC) about the local politics that gave birth to the Duterte legend.